Cenografias e ethos construídos em memoriais autobiográficos de uma profissão docente - Trindade, Rosinélio Rodrigues da (2022)
This thesis aims at understanding the teaching ethos in the process of continuing education in the National Program for the Training of Teachers of Basic Education - PARFOR- and to give visibility to the scenographies built on the teaching work in autobiographical memorials of professional training. The corpus was produced from the collection and organization of memorials prepared by students/teachers of the Letras-Portuguese class 2015/Cametá-PA, in the February 2018 stage. The research is based on discursive and ergological theoreticalmethodological approaches. The first is anchored in the assumptions of French Discourse Analysis (AD), from the perspective of Dominique Maingueneau, focusing on the materiality of speech and its conditions of production, apprehended through the notions of speech genre, scene of enunciation and discursive ethos. Regarding the ergological perspective, the assumptions of Yves Schwartz were followed, considering the humanist character with which the philosopher has brought considering the complexity of the work activity behind work. The concepts of antecedent norms, renormalization and rationality of the body-self were mobilized, considering the principle according to which debates on norms and values are instituted to resingularize human activity at work. From the methodological point of view, a simultaneous use was made of bibliographic research and qualitative field research. The scenographies gathered in the professional trajectories - which sometimes explain a constituted knowledge, legitimized by the academic instance, or an invested knowledge, the result of the unique experiences produced, in daily work, - have a fundamental role in the construction of the ethos that appears in the autobiographical memorials. Two enunciative movements/regularities, around which the scenes of the profession are constituted, the scenes of valorization and the scenes of resigularization of the teaching work, point to this conclusion